Analisis Penerapan Pembelajaran Berdiferensiasi Pada Mata Pelajaran Bahasa Indonesia Di Kelas III SD Negeri 01 Manokwari - Duma, Lorini; Muflihah, Siti; Zahra, Siti Fatimahtun; Aristanto, Aristanto (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
This study aims to analyze the application of differentiated learning in the Indonesian language subject in grade III of SD Negeri 01 Manokwari using a descriptive qualitative approach. Data collection techniques were carried out through observation, interviews, and documentation of teachers and grade III students. The results of the study show that teachers have implemented differentiated learning by considering the learning needs of students, including aspects of learning readiness, interests, and learning profiles. This implementation begins with an initial assessment through reading and writing tests and observation of students' learning styles. Content differentiation is carried out by providing teaching materials at different levels of difficulty and using varied media. Process differentiation is reflected in the use of diverse learning methods such as group discussions, paired work, and individual assignments. Product differentiation is realized by giving students the option to convey their learning results, either in oral presentations, pictures, or making summaries. A conducive learning environment also supports the learning process by providing comfort and flexibility for students in learning. Although it has been running quite well, the implementation of differentiated learning still faces obstacles such as limited time, lack of learning resources, and lack of training for teachers. Therefore, more support is needed in terms of resources and teacher training so that differentiated learning can take place more optimally and sustainably, so as to improve the quality of learning and better facilitate the diversity of students' learning needs.